(untitled) (Vietnam Journal of Community Medicine, 2026)
neonates at Thai Binh Children’s Hospital from 2024 to 2025. Methods: This retrospective cross-sectional study included 155 preterm neonates (<37 weeks of gestation) diagnosed with respiratory distress and admitted for inpatient treatment between January 1, 2024 and December 31, 2025. Results: Most patients were male (64.52%). The mean gestational age was 32.99 ± 3.01 weeks, with the majority in the 32 to <37 weeks group. Low birth weight (<2500 g) was observed in 72.26% of cases. The leading cause of respiratory distress was neonatal infection (46.45%), this was followed by pulmonary conditions, with pneumonia accounting for 38.06% and respiratory distress syndrome for 32.9%.Overall, 71% of patients recovered and were discharged, 12% died or were discharged against medical advice and 17% were referred to higher-level facilities. Poor treatment outcomes were significantly associated with lower gestational age, low birth weight, severe respiratory distress, need for respiratory support (invasive and non-invasive ventilation), use of vasoactive agents, and total parenteral nutrition (p < 0.05). No significant associations were found between outcomes and sex, mode of delivery, or number of antibiotics used. Conclusion: Neonatal infection and respiratory distress syndrome were the primary causes of respiratory distress in preterm neonates. Most patients had favorable outcomes, with a high rate of recovery and discharge. Early diagnosis and timely intervention are crucial for improving prognosis.